Disaster information media in ASEAN countries: a paired comparison method - Muhammad Yudhi Rezaldi,; Rabiah Abdul Kadir,; Mohamad Taha Ijab,; Azlina Ahmad, (Penerbit Universiti Kebangsaan Malaysia, 2020)
The media, as a tool for creating awareness and educating the community, plays an important role in conveying information about natural disasters. Numerous types of information media can be used at present. However, the most widely used media type, the delivery stages and the role of media in disaster management remain under researched. This study performs a literature review of various information media for natural disasters used in ten Association of Southeast Asian Nations (ASEAN) countries as a reference for creating disaster information media, which will be improved in future research. Information is obtained by reviewing 79 papers. Media information analysis is conducted using the paired comparison method. The components used for comparison cover media types, delivery phase and role in disaster management. Results show that the media used in ASEAN countries are similar: print media (e.g. brochures, posters, and newspapers), and electronic media (e.g. radio, television, Internet and modelling). The results of the analysis also indicate that the most commonly used disaster information media are electronic media, which deliver information during a disaster to convey information on events and losses incurred. Disaster simulation modelling, including evacuation routes and rescue efforts, is the information media that should be more widely used in the future. Information should be disseminated before a disaster occurs, very important apply situational crisis communication theory to an institution of disaster management in making the right decisions, strategic, and useful. Thereby rendering it useful in reducing the loss of life and damage to infrastructure caused by a disaster.